The Perraults : a family of letters in early modern France - Rabinovitch, Oded (Cornell University Press, 2018)
"This book shows how the family strategy of the Perraults interacted with their literary and scientific projects, leading to a revision of our image of the major cultural institutions of the seventeenth century"--